Acute cerebrovascular event in a COVID-19 positive patient immediately after commencing non-invasive ventilation. Issue 9 (8th September 2020) - Burkert, Julia; Patil, Shashank
Abstract : A 71-year-old man presented to the emergency department (ED) with low oxygen saturations and symptoms consistent with COVID-19 infection. Apart from a small left-sided ischaemic stroke 10 years prior with very minor residual deficit, he had been well and in full-time employment until development of symptoms. Within minutes of commencing non-invasive ventilation (NIV) in the ED, he developed a complete left-sided paralysis and hemineglect. This case highlights the significance of the prothrombotic complications associated with COVID-19 infection. It also raises the question whether pressure changes upon commencing NIV could lead to clot migration.